Proteasome modulating agents induce rAAV2-mediated transgene expression in human intestinal epithelial cells - Tang, Shiue-Cheng; Sambanis, Athanassios; Sibley, Eric (Biochemical and biophysical research communications, 2005)
Intestinal gene transfer offers promise as a therapeutic option for treatment of both intestinal and non-intestinal diseases. Recombinant adeno-associated virus serotype 2, rAAV2, based vectors have been utilized to transduce lung epithelial cells in culture and in human subjects. rAAV2 transduction of intestinal epithelial cells, however, is limited both in culture and in vivo. Proteasome-inhibiting agents have recently been shown to enhance rAAV2-mediated transgene expression in airway epithelial cells. We hypothesized that similar inhibition of proteasome-related cellular processes can function to induce rAAV2 transduction of intestinal epithelial cells. Our results demonstrate that combined treatment with proteasome-modulating agents MG101 ( N-acetyl- l-leucyl- l-leucyl- l-norleucine) and Doxorubicin synergistically induces rAAV2-mediated luciferase transgene expression by >400-fold in undifferentiated Caco-2 cells. In differentiated Caco-2 monolayers, treatment with MG101 and Doxorubicin induces transduction preferentially from the basolateral cell surface. In addition to Caco-2 cells, treatment with MG101 and Doxorubicin also results in enhanced rAAV2 transduction of HT-29, T84, and HCT-116 human intestinal epithelial cell lines. We conclude that MG101 and Doxorubicin mediate generic effects on intestinal epithelial cells that result in enhanced rAAV2 transduction. Use of proteasome-modulating agents to enhance viral transduction may facilitate the development of more efficient intestinal gene transfer protocols.